Electrochemical Confinement Effects for Innovating New Nanopore Sensing Mechanisms. Issue 6 (30th April 2018) - Ying, Yi‐Lun; Gao, Rui; Hu, Yong‐Xu; Long, Yi‐Tao
Abstract: Nanopores employ a confined space for electrochemical sensing of high‐throughput individual biomolecules in solution. Tremendous research efforts over the last two decades have made nanopore techniques become a powerful single‐molecule tool in nanotechnology and biotechnology. The most general mechanism of nanopore sensing is based on a volume‐exclusion effect. However, the increasing demands on revealing the single‐molecule chemistry and biophysics require that nanopores not only provide structural/conformational/sequencing information but also directly read the dynamic functional properties of single molecules. Here, the concept of electrochemical confinement effects in nanopores for developing new sensing mechanisms is proposed and extended. Three examples of electrochemical confinement effects are demonstrated here including the confinement of strong interactions between pore and analyte, the electron‐transfer process, and the subwavelength light inside nanopores. In particular, the latter two effects lead to novel detection mechanisms beyond volume exclusion, which can efficiently convert the dynamic function/structure of single molecules into ionic signatures or optical patterns. These achievements give rise to the possibility of adopting nanopore sensing in a wider range of future applications in both life and material sciences. Abstract : Electrochemical confinement effects in nanopores are proposed and extended for developing new sensing mechanisms. The electrochemical confinement of the strong interaction between a nanopore and an analyte, the electron‐transfer process, and even subwavelength light inside nanopores, which would prompt the nanopore to further reveal single‐molecule chemistry and biophysics, are discussed.